2021
DOI: 10.1108/bfj-12-2020-1090
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of traditional foods from a consumer's perspective: a review of methods and highlights

Abstract: PurposeThis review aims to summarize some of the relevant methodologies used to study traditional foods evaluated from the consumers' perspective. The analysis provided in this review will shed light on the methods as a valuable tool to stimulate research in traditional to promote cultural and nutritional revaluation of these products.Design/methodology/approachA systematic literature review was performed on 60 articles related to the study of traditional foods from the consumer's perspective.FindingsTen metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 57 publications
(103 reference statements)
0
3
0
Order By: Relevance
“…TFPs are a subject of many researches in recent decades (Dogan et al, 2017;Barska and Wojciechowska-Solis, 2018;Kocman, 2018;Silvestri et al, 2020;García-Barrón et al, 2021). However, the research approaches are different (quality, perception, consumption, distribution, impacts, innovations and other) (Guerrero et al, 2010;Mohamed Shaffril et al, 2015;Nguyen et al, 2018;Kovács et al, 2022).…”
Section: Traditional Food In Researchesmentioning
confidence: 99%
“…TFPs are a subject of many researches in recent decades (Dogan et al, 2017;Barska and Wojciechowska-Solis, 2018;Kocman, 2018;Silvestri et al, 2020;García-Barrón et al, 2021). However, the research approaches are different (quality, perception, consumption, distribution, impacts, innovations and other) (Guerrero et al, 2010;Mohamed Shaffril et al, 2015;Nguyen et al, 2018;Kovács et al, 2022).…”
Section: Traditional Food In Researchesmentioning
confidence: 99%
“…Indonesia consists of various regions, diverse ethnic groups that have various characteristics including in their traditional foods. Traditional food is a cultural heritage of a region and strengthens the identity and food sovereignty of the community (García- Barrón et al, 2021). With a very large number, there are more than 5,300 traditional culinary delights that are the original foods of the Indonesian nation (Parantika & Jenica, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…With a very large number, there are more than 5,300 traditional culinary delights that are the original foods of the Indonesian nation (Parantika & Jenica, 2022). Traditional food is defined as products that are often consumed or associated with customs/celebrations and/or specific seasons, usually passed down to the next generation, made using specific methods according to gastronomic heritage, with little or no processing/manipulation, distinguished and known for their sensory characteristics, and associated with a particular region or country (García-Barrón et al, 2021;Guerrero et al, 2009). Culinary or traditional food is often also referred to as market snacks/Jajanan Pasar (Andriani et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…At the methodological level, traditional foods have been studied from different perspectives, from quantitative methods, such as hedonic tests, conjoint analysis, sorting tests, and surveys with attitudinal questionnaires, to more flexible qualitative methods, including focus groups and depth interviews, or projective methods, such as the WA technique [ 10 ]. In the case of the WA technique, it has been observed that “traditional foods” have been among the most studied food categories through this technique, allowing a rapid approach to the object of study, due to its ease of use and versatility [ 11 ].…”
Section: Introductionmentioning
confidence: 99%